Sevoflurane exposure may cause dysplasia of dendritic spines and result in fine motor dysfunction in developing mouse through the PI3K/AKT/mTOR pathway - Zhong, Linhong; Ma, Xiaofan; Niu, Yixuan; Zhang, Lei; Xue, Zhenyu; Yan, Jia; Jiang, Hong (Frontiers in Neuroscience, 2022)
Sevoflurane has become one of the most widely used volatile anesthetics in pediatric surgery. However, sevoflurane exposure may interfere with dendritic development and synaptogenesis, resulting in brain function impairment. The PI3K/AKT/mTOR pathway plays an important role in dendritic development and synaptic plasticity. Here we investigated whether sevoflurane exposure affects the morphological proportions of dendritic spines in developing mouse and explored the role of the change of plasticity of dendritic spines in sevoflurane-induced neurodevelopmental toxicity. The related signaling pathway was also examined. C57BL/6 mice at postnatal day (PND) 7 were exposed to 2% sevoflurane for 3 hours. The PI3k/AKT/mTOR agonist IGF-1 or the mTOR phosphorylation inhibitor KU0063794 was intraperitoneally injected 30 min before sevoflurane or O2 exposure at PND7. Hippocampi were harvested 6 hours after sevoflurane exposure. Western blotting was applied to measure the protein expression of PI3K/AKT/mTOR pathway phosphorylation. At PND14, brains from all groups were harvested for Golgi staining, and the morphology of dendritic spines of hippocampal neurons was observed by an oil immersion lens. When the mice grew to adolescence (PND48), fine motor function was measured by the Beam walking test. Here we showed that exposure to 2% sevoflurane for 3 hours decreased the proportion of thin dendritic spines and increased the proportion of mushroom dendritic spines, but not changed the density of the dendritic spines. Sevoflurane exposure also suppressed the phosphorylation of the PI3K/AKT/mTOR pathway in immature mice hippocampi, and eventually led to long-term fine motor dysfunction. Meanwhile, IGF-1 pretreatment could rescue and KU0063794 pretreatment could aggravate the impairment induced by sevoflurane. In conclusion, sevoflurane exposure may cause a change of proportions of the types of dendritic spines through impacting the phosphorylation expression of the PI3K/AKT/mTOR pathway, and eventually led to long-term fine motor dysfunction in developing mouse.